2018
DOI: 10.31616/asj.2018.12.6.1100
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Postoperative Urinary Retention Following Elective Posterior Lumbar Spine Surgery: A Prospective Study

Abstract: Study DesignProspective observational study.PurposeTo determine the incidence of postoperative urinary retention (POUR) in patients undergoing elective posterior lumbar spine surgery and identify the risk factors associated with the development of POUR.Overview of LiteraturePOUR following surgery can lead to detrusor dysfunction, urinary tract infections, prolonged hospital stay, and a higher treatment cost; however, the risk factors for POUR in spine surgery remain unclear.MethodsA prospective, consecutive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 17 publications
3
41
1
Order By: Relevance
“…The authors speculate that POUR may have a greater impact on the duration of stay, particularly, when procedures, such as microdiscectomy and lumbar decompressions, are performed on a day care basis or when the patients have a shorter postoperative stay. (14) Our study shows that diabetics was one of the individual risk factors for development of POUR. Numerous studies also have reported higher rates of POUR in diabetics.…”
Section: Discussionmentioning
confidence: 55%
“…The authors speculate that POUR may have a greater impact on the duration of stay, particularly, when procedures, such as microdiscectomy and lumbar decompressions, are performed on a day care basis or when the patients have a shorter postoperative stay. (14) Our study shows that diabetics was one of the individual risk factors for development of POUR. Numerous studies also have reported higher rates of POUR in diabetics.…”
Section: Discussionmentioning
confidence: 55%
“…Despite some reports supporting a correlation between the volumes of IV fluid administered during surgery and the incidence of POUR in patients undergoing major surgeries ( 122 125 ), this association has not been observed in patients undergoing spine surgeries ( 15 , 111 ). In a retrospective study including 397 patients who had undergone elective cervical, thoracic and lumbar surgery, Altschul et al ( 116 ) reported an increased incidence of POUR in those patients with longer operative times.…”
Section: Fluid Management and Postoperative Complications In Spine Sumentioning
confidence: 81%
“…Postoperative urinary retention (POUR) is defined as an acute inability to void when the bladder is full after surgery, leading to patient's anxiety, discomfort, urinary tract infections, delayed hospital discharge and/or increased readmission rates ( 114 119 ). Most cases of POUR are associated with surgeries performed on the lumbar spine ( 15 , 116 , 119 121 ). Lumbar spine surgeries commonly involve the use of a Foley catheter which may cause urethral irritation and edema or reactive increase in tone of the bladder outlet, thereby contributing to POUR ( 120 ).…”
Section: Fluid Management and Postoperative Complications In Spine Sumentioning
confidence: 99%
See 1 more Smart Citation
“…The medical comorbidities are not a contraindication for PTELD under LA 8 , 11 . In fact, the negativities of GA on the patient’s visceral function (POUR-post-operative urinary retention) and cognitive dysfunction are not hidden and may have some critical role in immediate post-operative period in spine surgeries 34 . One patient of our series was operated under GA and he took one week to recover his bladder function.…”
Section: Discussionmentioning
confidence: 99%